2020
DOI: 10.1007/s42452-020-2100-1
|View full text |Cite
|
Sign up to set email alerts
|

Fibers of cellulose sugarcane bagasse with bromelain enzyme immobilized to application in dressing

Abstract: The enzymes have been gaining more importance in different fields, among the most important the pharmaceutical field. However, due to the protein nature of the enzymes, a significant part of them presents high instability under certain conditions of use. A great way to stabilize them is to use immobilization techniques. Bromelain from pineapple has shown potential to be used in the treatment of burn-like skin injuries and superficial injuries. Biocatalytic textile fibers from cellulose of sugarcane bagasse wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It was noted that the lowest LC% when using a ratio of 1:30 was likely caused by effect of net charge equilibrium in the suspension, which exhibited low attraction for bromelain to interact with and form the composite. The LC% value obtained from this study was relatively low compared to that reported using the ionotropic gelation technique (14–16) , and also other technologies such as covalent immobilizations (2–68%), ,, encapsulation processes using double emulsion solvent evaporation methods (4–5%), , and absorption process (7–8%) . For industrial applications, high enzyme loading capacity is important as it can increase the process efficiency and reduce material quantity as well as material cost.…”
Section: Results and Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It was noted that the lowest LC% when using a ratio of 1:30 was likely caused by effect of net charge equilibrium in the suspension, which exhibited low attraction for bromelain to interact with and form the composite. The LC% value obtained from this study was relatively low compared to that reported using the ionotropic gelation technique (14–16) , and also other technologies such as covalent immobilizations (2–68%), ,, encapsulation processes using double emulsion solvent evaporation methods (4–5%), , and absorption process (7–8%) . For industrial applications, high enzyme loading capacity is important as it can increase the process efficiency and reduce material quantity as well as material cost.…”
Section: Results and Discussionmentioning
confidence: 60%
“…Enzyme immobilization could be achieved using covalent and noncovalent processes. Covalent bindings using cross-linking agents have been applied for enzyme immobilization onto cellulose fibers from sugar cane bagasses, , chitosan materials, clay/chitosan composites, , and cellulose ultrafine fibers . Despite this technique offering high stability of adsorbed enzymes to the environmental conditions such as pH, temperature, ionic strength, and biomolecule concentration, its main disadvantages are the poor knowledge of enzyme structure, the additional purification procedures to eliminate residual toxic reagents, and the lengthy, labor-intensive process.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme shows fibrinolytic, anti-inflammatory, thrombolytic and edematous activities [2][3][4][5][6], which, as well, have been applied in the treatment of enkephalin [7] and leukemia, in anticancer activity [8], in the treatment of allergic airway disease [9][10][11] and in cosmetic compositions [12,13]. Bromelain has been used for dental care, in digestive aid and in food industries, such as breweries, meat processing, textiles and other [14][15][16][17][18][19]. Therefore, because the important benefits found for the health of humans and properties mentioned, commercial bromelain reaches a high price, being sold at USD 1000 per kg [4].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration by polarization reduces the hydraulic permeability of the membrane and its occurrences decrease the membrane performance. The decrease in permeate flux reduces the diffusion coefficient [1,16].…”
Section: Introductionmentioning
confidence: 99%